The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s00259-016-3452-z
|View full text |Cite
|
Sign up to set email alerts
|

The asphericity of the metabolic tumour volume in NSCLC: correlation with histopathology and molecular markers

Abstract: The ASP of primary NSCLCs on FDG PET images is associated with tumour dimensions and molecular markers of proliferation and angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 40 publications
1
45
0
Order By: Relevance
“…However, compared to the present study investigating SSTR-PET, heterogeneity parameters were derived from [ 111 In-DTPA 0 ]octreotide scintigraphy [44], which has a lower affinity to SSTR2A compared to its PET counterparts [45]. Moreover, entropy and asphericity differ in their equations, which also serves as a possible explanation for the different results: The latter one quantitates the deviation from spherical of the shape of the MTV, and it takes both the mean surface S and the mean volume V into account [44,46]. On the contrary, entropy considers I as the voxel value in the ROI and P(I) as the probability of the occurrence of that pixel value [47].…”
Section: Discussionmentioning
confidence: 99%
“…However, compared to the present study investigating SSTR-PET, heterogeneity parameters were derived from [ 111 In-DTPA 0 ]octreotide scintigraphy [44], which has a lower affinity to SSTR2A compared to its PET counterparts [45]. Moreover, entropy and asphericity differ in their equations, which also serves as a possible explanation for the different results: The latter one quantitates the deviation from spherical of the shape of the MTV, and it takes both the mean surface S and the mean volume V into account [44,46]. On the contrary, entropy considers I as the voxel value in the ROI and P(I) as the probability of the occurrence of that pixel value [47].…”
Section: Discussionmentioning
confidence: 99%
“…In that context, the appeal of any single parameter that could complement tumor volume to further characterize functional tumor uptakes from PET images and can be relatively quickly implemented in clinical practice is strong. The shape descriptor sphericity has been recently highlighted as one such new measure that could provide complementary prognostic value for patients stratification in both H&N and NSCLC [7][8][9][10]. In addition, it could be also considered as indirectly quantifying uptake heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a 3D shape descriptor named asphericity has been proposed to indirectly assess uptake heterogeneity in FDG PET images with prognostic value in both head and neck and non-small cell lung cancer (NSCLC) [7][8][9]. It was also shown to be correlated with underlying histopathological features and molecular markers [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among parameters from positron emission tomography/computed tomography with [ 18 F] uorodeoxyglucose (FDG-PET/CT), asphericity (ASP) is a parameter that re ects shape irregularity of the primary tumor's metabolic tumor volume (MTV), combining metric and metabolic features of the primary tumor. Three retrospective studies con rmed its independent prognostic value for progression-free (PFS) and overall survival (OS) in patients with NSCLC (13)(14)(15). The largest study (311 patients, UICC stage I-III) further showed that ASP, with an optimal cut-off of > 19.5%, could identify patients with UICC stage II treated by surgery and adjuvant chemotherapy with high ASP and reduced PFS (median, 11 months vs. not reached) and OS (22 months vs. not reached) (15).…”
Section: Introductionmentioning
confidence: 99%